Combined Effects of Elevated pCO2 and Warming Facilitate Cyanophage Infections - Cheng, Kai; Van de Waal, Dedmer B.; Niu, Xiao Ying; Zhao, Yi Jun (Frontiers in Microbiology, 2017)
Elevated pCO2 and warming are generally expected to influence cyanobacterial growth, and may promote the formation of blooms. Yet, both climate change factors may also influence cyanobacterial mortality by favouring pathogens such as viruses, which will depend on the ability of the host to adapt. To test this hypothesis, we grew Plectonema boryanum IU597 under two temperature (25 and 29°C) and two pCO2 (400 and 800 µatm) conditions for 1 year, after which all treatments were re-exposed to control conditions for a period of 3 weeks. At several time points during the 1 year period, and upon re-exposure, we measured various infection characteristics of it associated cyanophage PP, including the burst size, latent period, lytic cycle and the efficiency of plaquing. As expected, elevated pCO2 promoted growth of P. boryanum equally over the 1 year period, but warming did not. Burst size increased in the warm treatment, but decreased in both the elevated pCO2 and combined treatment. The latent period and lytic cycle both became shorter in the elevated pCO2 and higher temperature treatment, and were further reduced by the combined effect of both factors. Efficiency of plaquing decreased in the elevated pCO2 treatment, increased in the warm treatment, and increased even stronger in the combined treatment. These findings indicate that elevated pCO2 enhanced the effect of warming, thereby further promoting the virus infection rate. The re-exposure experiments demonstrate adaptation of the host leading to higher biomass build-up with elevated pCO2 over the experimental period, and lower performance upon re-exposure to control conditions. Similarly, virus burst size and efficiency of plaquing increased when given warm adapted host, but were lower as compared to the control when the host was re-exposed to control conditions. Our results demonstrate that adaptation but particularly physiological acclimation to climate change conditions favored viral infections, while limited host plasticity and slow adaptation after re-exposure to control conditions impeded host biomass build-up and viral infections.